A randomized, placebo‐controlled study to evaluate the efficacy and safety of adding omarigliptin to insulin therapy in Japanese patients with type 2 diabetes and inadequate glycaemic control. Issue 6 (17th February 2021) - Kadowaki, Takashi; Seino, Yutaka; Kaku, Kohei; Okamoto, Taro; Kameya, Miho; Sato, Asako; Hirano, Tomona; Oshima, Nobuyuki; Gantz, Ira; O'Neill, Edward A.; Engel, Samuel S.; ,
Abstract: Aim: To evaluate the efficacy and safety of adding the once‐weekly oral dipeptidyl peptidase‐4 inhibitor omarigliptin to treatment of Japanese patients with type 2 diabetes and inadequate glycaemic control on insulin monotherapy. Materials and Methods: In a 52‐week clinical trial, Japanese patients on insulin monotherapy were randomized to once‐weekly omarigliptin 25 mg ( N = 123) or placebo ( N = 61) for a 16‐week, double‐blind, placebo‐controlled period. After Week 16, patients continued or switched to omarigliptin for a 36‐week open‐label period. Results: From a mean baseline of approximately 8.8%, the Week 16 least squares mean changes in HbA1c were −0.61% (omarigliptin) and 0.29% (placebo); the between‐group difference was −0.90% ( p < .001). At Week 52, the mean change from baseline in HbA1c was −0.57% in both the group on omarigliptin for 52 weeks and the group on omarigliptin for 36 weeks (switched from placebo at Week 16). During the first 16 weeks of treatment, the incidences of adverse events (AEs), serious AEs, drug‐related AEs and discontinuation from trial medication because of an AE were similar in both groups. A slight increase in incidence of symptomatic hypoglycaemia was observed in the omarigliptin group ( n = 13 [10.6%]) compared with placebo ( n = 4 [6.6%]). No severe hypoglycaemia was reported during the study. No new safety signals emerged with treatment beyond Week 16 through Week 52. Conclusion: The addition of once‐weekly omarigliptin to insulin therapy for up to 52 weeks was generally well tolerated and provided clinically meaningful improvement in glycaemic control throughout the trial period. ClinicalTrials.gov: NCT02906709